EVALUASI PEMBANGUNAN KESEHATAN DALAM UPAYA PENURUNAN ANGKA KEMATIAN IBU DAN BAYI DI KABUPATEN MALANG - Rosyidatuzzahro Anisykurlillah; Patriani Wilma Eunike Supit (Halu Oleo University, 2023)
Health is one of the basic human rights that must be guaranteed by the state. The success of health development is reflected in the reduction in maternal and child mortality as an indicator of successful regional development. The high maternal mortality and infant mortality rates are a strategic issue in the 2021-2026 Regional Medium-Term Development Plan (RPJMD) of Malang Regency. This study aims to describe and evaluate health development as an effort to reduce maternal and infant mortality in Malang Regency. The type of research used is descriptive with a qualitative approach. The evaluation method used is CIPP which consists of Context, Input, Process, and Product. The CIPP technique is used for sectoral development assessment, in this case the health sector for mothers and babies with a regional apparatus, namely the Health Office of Malang Regency. The data analysis used was Creswell's qualitative data analysis. The evaluation results show that there are still several obstacles in the development of maternal and infant health as an effort to reduce maternal and infant mortality in Malang Regency. These obstacles include: not optimal quality and quantity of paramedics, affordability and access to health facilities are not evenly distributed in several villages, as well as some people who prefer traditional birth attendants in providing assistance because the community considers it cheaper.